Level and Sociodemographic Determinants of Physical Dependencies in Middle-Aged Women of Rawalpindi District: A Cross-Sectional Study - Kanwal, Tooba; Ebad Ur Rehman, Mohammad; Basit, Jawad; Zaidi, Narjis (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Background: Data regarding possible risk factors/determinants for physical dependence in women in their early middle age and early adulthood was scarce. It is critical to identify the risk factors for physical dependence to lay the groundwork for the development of primary health interventions for women in their early adulthood and Middle Ages. Objectives: This study was conducted to determine the level of physical dependence among middle aged women of Rawalpindi and to identify socio-demographic risk factors for physical dependence in young adult/middle aged women. Materials and Methods: Participants with physical disabilities that occurred in childhood, those with hereditary diseases, and those with psychiatric illnesses preventing them from filling out the questionnaire were excluded from the study. The level of physical dependence was assessed using Barthel Index (BI) and 36-item Short Form Health Survey (SF-36). Descriptive statistics, student t-test, and Pearson correlation were applied. Results: A total of 176 women were included in our study. The mean age of participants was 50.1 years. The mean BI score was 94. The mean Perceived Stress Scale score was 22.6. The PSS score was inversely correlated with role limitation due to physical function, well-being, social function, pain, and general health scoresthe . Age was inversely correlated with physical function, well-being, social function, pain, and general health scores. Conclusion: Occupation status, presence of non-communicable disease, body aches, age, and stress are important risk factors that may contribute to the rising levels of disability and lower quality of life in middle-aged women.